Synthesis of Four Stereoisomers of (S)‐2‐Methylpent‐3‐yl 3, 13‐Dimethylpentadecanoate, a Sex Pheromone of the Bagworm Moth Clania variegate, Using Stereospecific Inversion of Secondary Sulfonates as a Key Step. Issue 30 (4th September 2013) - Taguri, Tomonori; Yamamoto, Masanobu; Fujii, Toru; Muraki, Yuta; Ando, Tetsu
Abstract: Females of some lepidopteran species produce novel sex pheromones with a methyl‐branched structure, such as 2‐methylpent‐3‐yl 3, 13‐dimethylpentadecanoate secreted by the bagworm moth Clania variegate . Recently, we have established a simple preparative method for the synthesis of methyl‐branched building blocks by utilizing an SN 2 reaction of chiral secondary tosylates derived from ( S )‐ and ( R )‐propylene oxides. The usefulness of these building blocks was demonstrated by their application in the synthesis of all four stereoisomers of an acid moiety in the bagworm pheromone. The enantiomeric purities of all building blocks were confirmed by enantioselective HPLC analysis. We found that a secondary mesylate was superior to the corresponding tosylate because it avoided an elimination side reaction, and racemization in the SN 2 reaction was not observed even at high temperature (150 °C). Finally, each optically active acid was esterified with ( S )‐2‐methyl‐3‐pentanol, which was synthesized by a new route starting from ( S )‐valine. Abstract : A simple route to methyl‐branched building blocks has been developed by utilizing an SN 2 reaction of chiral secondary sulfonates derived from ( S )‐ and ( R )‐propylene oxides. The usefulness of these building blocks was demonstrated by the stereospecific synthesis of all four stereoisomers of a bagworm pheromone.